2016
DOI: 10.1002/pc.23999
|View full text |Cite
|
Sign up to set email alerts
|

Fracture toughness of woven glass and carbon reinforced hybrid and non‐hybrid composite plates

Abstract: The fracture toughness and strength of materials are adversely affected by the cracks in the materials, which can be induced during manufacturing, assembly, and usage. In this study, the effect of crack length and crack location on the fracture toughness of woven glass and carbon reinforced hybrid and non-hybrid composite plates were investigated experimentally and numerically. For this purpose, glass/epoxy (G 8 ), and carbon/epoxy (C 8 ) non-hybrid composite plates and glass-carbon/epoxy (G 2 C 4 G 2 ), and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
1
18
0
1
Order By: Relevance
“…Also, the fracture toughness values increased for the same reinforcement fabric types, when the crack length was increased. A survey of literature on the effect of crack length on the fracture toughness has revealed that the findings presented in this article are in comply with the results already found by other authors . Table shows that each of natural fibers (or yarns) has different strength values.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Also, the fracture toughness values increased for the same reinforcement fabric types, when the crack length was increased. A survey of literature on the effect of crack length on the fracture toughness has revealed that the findings presented in this article are in comply with the results already found by other authors . Table shows that each of natural fibers (or yarns) has different strength values.…”
Section: Resultssupporting
confidence: 90%
“…Fracture behavior of orthotropic materials is more complex because of nature of these materials. As well known, plastic zone formation during damage is not observed in brittle materials unlike ductile materials . As a consequence, crack in the brittle materials is more danger than the ductile materials in terms of durability of structures.…”
Section: Introductionmentioning
confidence: 96%
“…This is valid for materials with linear-elastic structure as well as for small-scale deformations at the crack tip under static conditions. [30] For twodimensional analysis, J-integral is defined as in Equation (12).…”
Section: Finite Element Analysesmentioning
confidence: 99%
“…2). When the applied normal stress reaches the failure stress, the stress intensity factors K I and K II become the critical stress intensity factor (K IC and K IIC ), which is taken as the fracture toughness of the composite specimens [30,31]. The stress intensity factors ahead of the crack tip for Arcan test sample are calculated by using Eq.…”
Section: àámentioning
confidence: 99%